Hepatitis E virus infection among blood donors in Zhengzhou - ZHAO Hongna; WEI Yueguang; YAN Lumin; TU Tiantian; WANG Shumin; WEI Yihui; WANG Yifang; ZHAO Lei; CHEN Mingjun (Zhongguo shuxue zazhi)
[Objective] To analyze the infection status of hepatitis E virus (HEV) among blood donors in Zhengzhou, so as to provide data support for formulating local blood screening strategies. [Methods] Random samples from blood donors from January to December 2022 were tested for HEV RNA using PCR technology. Reactive samples were sequenced for gene analysis, and the donors were followed up. [Results] Among 21 311 samples, 3(0.14‰) were reactive for HEV RNA, all of whom were male. Genetic sequencing results revealed that one strong positive sample was genotype 4, while sequencing failed for the other two due to low viral load. A follow-up of 25 strong positive donors showed that ALT significantly increased on day 7 after donation, anti-HEV IgM and anti-HEV IgG turned positive. On day 21, ALT returned to normal, and on day 35, HEV RNA turned negative. Notably, anti-HEV IgM and anti-HEV IgG persisted until day 482. [Conclusion] There is HEV infection among blood donors in Zhengzhou, and it is necessary to expand the screening scope to comprehensively explore the prevalence and genotype distribution of HEV among blood donors.